Pengembangan Learning Management System (LMS) dengan Pemrograman PHP untuk Materi Digital Marketing - Devi*, Erycha Arsita; Sarwanto, Sarwanto; Sukmawati, Fatma (Universitas Syiah Kuala, 2023)
In this digital era, it is not only the educational aspect that is progressing due to technology. The economic aspect is also experiencing technological progress. Just as conventional learning has developed into online learning, conventional commerce to digital commerce or digital marketing is the influence of technological developments. Therefore, researchers conducted a data collection survey by giving questionnaires to respondents to support media creation (LMS). The aim of this research is to create learning media, namely LMS Digital Marketing with the PHP programming language. This research uses a type of development research or Research and Development (RD) using the ILDF (Integrative Learning Design Framework) development model. The final result of this development research is a prototype web-based learning media (LMS) for digital marketing material which aims to help users understand digital marketing concepts without time and place limitations.